2020
DOI: 10.1016/j.eujim.2020.101139
|View full text |Cite
|
Sign up to set email alerts
|

Can network pharmacology identify the anti-virus and anti- inflammatory activities of Shuanghuanglian oral liquid used in Chinese medicine for respiratory tract infection?

Abstract: Introduction: Shuanghuanglian (SHL) oral liquid is a well-known traditional Chinese medicine preparation administered for respiratory tract infections in China. However, the underlying pharmacological mechanisms remain unclear. The present study aims to determine the potential pharmacological mechanisms of SHL oral liquid based on network pharmacology. Methods: A network pharmacology-based strategy including collection and analysis of putative compounds and target genes, network construction, Kyoto Encyclopedi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(20 citation statements)
references
References 74 publications
(71 reference statements)
1
18
0
1
Order By: Relevance
“…For example, estrogen signaling pathway, TNF signaling pathway, T-cell receptor signaling pathway, and B cell receptor signaling pathway were closely related to anti-inflammatory and immunoreactive activities. Meanwhile, the antibacterial and antiviral activity could be explicitly unscrambled from influenza A and tuberculosis signaling pathways [24,25]. All the predictions were highly consistent with the efficacy of SHLI in clearing heat and detoxifying, indicating the scientific nature and rationality of this study.…”
Section: Selection Of Index Components With Network Pharmacology Strategysupporting
confidence: 62%
“…For example, estrogen signaling pathway, TNF signaling pathway, T-cell receptor signaling pathway, and B cell receptor signaling pathway were closely related to anti-inflammatory and immunoreactive activities. Meanwhile, the antibacterial and antiviral activity could be explicitly unscrambled from influenza A and tuberculosis signaling pathways [24,25]. All the predictions were highly consistent with the efficacy of SHLI in clearing heat and detoxifying, indicating the scientific nature and rationality of this study.…”
Section: Selection Of Index Components With Network Pharmacology Strategysupporting
confidence: 62%
“…en, the molecular docking scores between the chemical compounds and the targets were assessed using AutoDock Vina [111]. Of note, a certain chemical compound is regarded as having high binding affinity to a target if the corresponding docking score is less than or equal to −5.0 [112,113].…”
Section: Molecular Docking Analysismentioning
confidence: 99%
“…Network pharmacology is a key method that integrates computer science and medicine to evaluate the molecular mechanisms of TCM. Several studies have shown that network pharmacology, molecular docking, and molecular dynamic simulation were effective to explore the underlying mechanisms and active compounds of TCM formula [ 15 , 16 ]. In this study, we aim to discover the active compounds and explore the potential mechanisms of HSXFF to cure COVID-19 by integrating network pharmacology and molecular docking.…”
Section: Introductionmentioning
confidence: 99%